Implementation of Greenhouse Technology to Support Bamboo Forest Conservation in Batara Village, Papring - Ikhwanul Qiram; Muhammad Naufal Aditya Fahmi; Andy Yudha Hutama; Gatot Sudarsono (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Kampoeng Batara, Papring is a community of forest-side residents who use bamboo as their main economic source of life. Greenhouse technology is expected to help the community in efforts to conserve bamboo forests that have been damaged by natural and human factors. This community service activity is carried out by implementing an automatic control system for the greenhouse watering irrigation system in overcoming environmental climate change. The types of seeds tested were pring pethung, watu, yellow, and pring-ori seeds. The greenhouse design in the form of a dome measuring 4x7 meters is used as a storage room for seeds, several sensors are connected to the acquisition and control system using Arduino-Uno. This system is designed to be able to help residents without a technical background where they can command complete control through temperature and humidity control of greenhouse spaces. The system test results show that the temperature and humidity of the room can be maintained at optimal conditions. The program output has shown the speed of root growth of seedlings within 3 weeks, suppressing stress that risks the death of seedlings. Conservation efforts through greenhouse technology with automatic sprinklers have an impact on supporting bamboo forest conservation efforts for the future of the Kampoeng Batara community.